2014
DOI: 10.1038/mtna.2014.21
|View full text |Cite
|
Sign up to set email alerts
|

Cell-type-specific, Aptamer-functionalized Agents for Targeted Disease Therapy

Abstract: One hundred years ago, Dr. Paul Ehrlich popularized the “magic bullet” concept for cancer therapy in which an ideal therapeutic agent would only kill the specific tumor cells it targeted. Since then, “targeted therapy” that specifically targets the molecular defects responsible for a patient's condition has become a long-standing goal for treating human disease. However, safe and efficient drug delivery during the treatment of cancer and infectious disease remains a major challenge for clinical translation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
162
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(169 citation statements)
references
References 127 publications
(155 reference statements)
1
162
0
2
Order By: Relevance
“…In the past decade, much attention has been focused on RNAbased aptamers that are emerging as safe delivery vehicles for targeted cancer therapeutics [19]. In addition to inhibitory function of selected targets, aptamers raised against transmembrane receptors rapidly internalize into the target cell through recycling of the bound receptor [20].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decade, much attention has been focused on RNAbased aptamers that are emerging as safe delivery vehicles for targeted cancer therapeutics [19]. In addition to inhibitory function of selected targets, aptamers raised against transmembrane receptors rapidly internalize into the target cell through recycling of the bound receptor [20].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…In addition to inhibitory function of selected targets, aptamers raised against transmembrane receptors rapidly internalize into the target cell through recycling of the bound receptor [20]. So far, various therapeutic cargoes have been successfully conjugated to aptamers, including anti-cancer drugs, toxins, radionuclides, and short therapeutic RNAs (siRNAs and miRNAs) [19,21,22]. The main advantages for aptamer use in vivo as cell targeting moieties, include the extraordinary high binding specificity, long-term stability, little to no immunogenicity and off target toxicity [23].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…The short nucleic acid-based aptamers are not expected to elicit significant neutralizing immunity that may become an issue, especially with repeated administration of even humanized antibodies. Aptamers have been used mostly to target nucleic acid-based biologic or therapeutic agents, such as siRNAs, microRNAs, or aptamers, and have been evaluated in preclinical in vitro and in vivo murine models for cancer and HIV (10,11). The use of therapeutic agents in the form of short nucleic acid-based cargo is attractive because conjugation to the targeting ligands, in contrast with conjugation to antibodies or peptides, is a simple procedure involving hybridization of short complementary sequences engineered at the end of the aptamer and its cargo.…”
Section: Targeted Drug Delivery With Oligonucleotide Aptamer Ligandsmentioning
confidence: 99%
“…Aptamers combine nanomolar range targetbinding affinities with exquisite target specificity, which makes them a versatile tool for diagnostics, in vivo imaging, and targeted therapeutics [12,[26][27][28][29]. Moreover, compared to protein antibodies, aptamers offer unparalleled advantages, as they can be chemically synthesized through a simple process, modified with a variety of functional groups and/or imaging reporters, and elicit little to no immunogenicity or toxicity in preclinical studies [30][31][32][33][34]. Taking advantage of these aptamer properties, our group recently demonstrated that synthetic aptamers can be successfully used as specific probes for flow cytometric analysis in vitro [35,36] and exhibit high tumor penetrating abilities and rapid tumor cells binding in vivo [37].…”
Section: Introductionmentioning
confidence: 99%